2022
DOI: 10.3390/ijms23116283
|View full text |Cite
|
Sign up to set email alerts
|

Iron Speciation and Iron Binding Proteins in Arthrospira platensis Grown in Media Containing Different Iron Concentrations

Abstract: Cyanobacteria are characterized by high iron content. This study investigated the effects of varying iron concentrations (1, 5, and 10 mg L−1) in the culture media on the biochemical composition and the iron bioaccumulation and speciation in Arthrospira platensis F&M-C256. Iron content measured in biomasses varied from 0.35 to 2.34 mg g−1 dry weight depending on the iron concentration in the culture media. These biomasses can be considered of interest for the production of spirulina-based supplements with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 39 publications
5
11
0
Order By: Relevance
“…In addition to this essential role, it has been reported by Bermejo et al (2008) [ 38 ] that this protein was able to bind iron in vitro. The data in the present study add additional evidence regarding the role of phycocyanin as an iron binding protein in vivo as recently suggested by Isani et al (2022a and b) [ 21 , 28 ]. Regarding P. tricornutum , Sutak et al (2012) [ 39 ] reported the presence of ISIP1 (iron starvation-induced protein 1), suggesting a role of this protein in iron uptake.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…In addition to this essential role, it has been reported by Bermejo et al (2008) [ 38 ] that this protein was able to bind iron in vitro. The data in the present study add additional evidence regarding the role of phycocyanin as an iron binding protein in vivo as recently suggested by Isani et al (2022a and b) [ 21 , 28 ]. Regarding P. tricornutum , Sutak et al (2012) [ 39 ] reported the presence of ISIP1 (iron starvation-induced protein 1), suggesting a role of this protein in iron uptake.…”
Section: Resultssupporting
confidence: 90%
“…Subsequently, to investigate the iron speciation in the soluble fractions, supernatants underwent SEC associated with sensitive metal detection in the fractions using atomic absorption spectroscopy (AAS), a hyphenated approach which is commonly used in metallomic studies [ 36 ] and had previously been applied to A. platensis [ 21 , 28 ]. Total proteins and iron measured in fractions after SEC are reported in Figure 3 and Figure 4 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is speculated that it may be related to the following factors: (1) Arthrospira platensis is rich in protein and a multitude of vitamins, β‐carotene and trace elements (selenium and zinc). It provides a balanced replenishment of essential nutrients, increases the body's immune function and alleviates and reduces the suppressive effect of radiation on the immune system (El‐Shall et al ., 2023); (2) Arthrospira platensis produces strong anti‐oxidant effect, which enhances the body's anti‐oxidant enzymes activity and capture free radicals, thus reducing the DNA damage caused by radiation‐induced free radical formation (El‐Shall et al ., 2023); and (3) Arthrospira platensis is enriched with iron elements and chlorophyll, which could promote the body's haematopoiesis and alleviate the inhibition of bone marrow haematopoiesis by radiation (Isani et al ., 2022).…”
Section: Functional Properties Of Arthrospira Platensismentioning
confidence: 99%